Symposium 13: Democratising Online Education through Innovative Methods and Tools: the case of Living Labs: Symposium Introduction - Karagiannidis, Charalampos; Koumpis, Adamantios (Proceedings of the International Conference on Networked Learning, 2008)
On November 20th, 2006, the Finnish EU Presidency launched a European Network of Living Labs for the "co-creation of innovation in public, private and civic partnership". This is the first step towards a new European Innovation System, entailing a major paradigm shift for the whole innovation process. A European Network of Living Labs is a collaboration of Public Private Partnerships where firms, public authorities and people work together in creating, prototyping, validating and testing new services, businesses, markets and technologies in real-life contexts, such as cities, city regions, rural areas and collaborative virtual networks between public and private players. The real-life and everyday contexts both stimulate and challenge research and development, as do public authorities and citizens not only participate in, but also contribute to the whole innovation process. The Living Lab concept is about moving out of laboratories into real-life contexts. In the past years, a number of national experiences can be mentioned across Western Europe, and more recently, an integration effort has been set out in a trans-European perspective. From a market and industrial perspective, Living Labs offer a research and innovation platform over different social and cultural systems, cross-regionally and cross-nationally. This is a natural move for ICT, life sciences and any innovation domain that deals with human and social problem solving and people's every day lives. However, this new approach to research for innovation is a huge challenge for research methodologies, innovation process management, public-private partnership models, IPRs, open source practices, development of new leadership, governance and financial instruments. This complexity increases remarkably with the international nature of a European Network of Living Labs, implying a set of large-scale experimentation platforms for new services, business and technology, market and industry creation within ICT environment. The aim of the proposed symposium is to further improve over this promising state of the art, by exploring success and failure stories and report on methodologies and toolsets for the pan-European deployment of Living Labs in the areas of networked learning, thus creating new opportunities for networking and best practice exchange between public entities, individuals, industry and academia. Through the replication of systems already operational and the integration of similar experiences across EU Member States, originally thought for the animation of democratic discussions and participative public opinion formation at local and regional level, we aim to revolutionise the networking and repeated interaction of Living Labs participants during the development and implementation of innovative networked learning projects. In the symposium we invite key professionals and researchers who shall contribute to the addressed subjects and have the opportunity to examine complementarities and explore the opportunities for useful synergies.